1993
DOI: 10.1093/intimm/5.11.1383
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IFN-γ in macrophages by lipopolysaccharide

Abstract: In this paper we report that macrophages can be stimulated to express detectable levels of IFN-gamma-specific mRNA. Macrophages from lipopolysaccharide (LPS)-responsive, C3H/OuJ mice are induced by LPS to increase steady-state levels of IFN-gamma-specific mRNA, while those from LPS-hyporesponsive C3H/HeJ mice are not. This interstrain variation is apparently the result of LPS-specific signal differences since macrophages derived from both Lpsn and Lpsd mouse strains are able to produce comparable levels of IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
2
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 0 publications
8
113
2
1
Order By: Relevance
“…Immunostaining demonstrated enhanced iNOS protein only in alveolar macrophages whereas IFN-␥ protein was present in both lymphocytes and macrophages. Expression of IFN-␥ has been noted previously in murine (25,26) and human (27) macrophages (reviewed in Ref. 28).…”
Section: Discussionmentioning
confidence: 68%
“…Immunostaining demonstrated enhanced iNOS protein only in alveolar macrophages whereas IFN-␥ protein was present in both lymphocytes and macrophages. Expression of IFN-␥ has been noted previously in murine (25,26) and human (27) macrophages (reviewed in Ref. 28).…”
Section: Discussionmentioning
confidence: 68%
“…In the human system, T cells that express the activation-dependent CD30 membrane antigen are the principal subset producing IFN-γ (Alzona et al, 1994). Recently production of IFN-γ by mononuclear phagocytes has also been described (Fultz et al, 1995).…”
Section: Cytokines Which Modulate Expression Of Mhc Class I Moleculesmentioning
confidence: 99%
“…IFN-+ gene knockout (IFN-+ -/-) mice, IFN-+ receptor gene knockout (IFN-+ R -/-) mice, as well as other IFN-+ -related gene knockout mice are extremely susceptible to intracellular pathogens compared to SCID or wild-type (WT) mice [5][6][7][8][9][10][11][12][13]. Whereas NK cells among lymphoid cells had been believed to be a major source of IFN-+ during early phase of infection, we and others have shown that antigen-presenting cells (APC) such as dendritic cells (DC) and macrophages produce large amounts of IFN-+ in response to interleukin (IL)-12 that is produced by APC upon microbial infection [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. In fact, amounts of IFN-+ produced by DC and macrophages are substantially larger than those produced by NK cells [14][15][16].…”
Section: Introductionmentioning
confidence: 99%